Nationhood from the schoolbag: A historical analysis of the development of secondary education in Trinidad and Tobago - Alleyne, Michael H. (OAS, 1996)
This book covers the history of secondary education in Trinidad and Tobago from the colonial era to independence, and onto the initial stages of nationhood. In addition to tracing the history of secondary education, it analyses the development of secondary education in Trinidad and Tobago by presenting valid theories in education and developmental economics. The book also examines the principal reports of committees and commissions that reviewed education and related matters in the country and made recommendations
Keywords: History of education